Program Gamifikasi Honda Dalam Peningkatkan Motivasi Dan Kompetensi Siswa Smk Jurusan Teknik - Adel lia Mardiana; Hasan Maksum; Dony Novaliendry (Jurnal Pendidikan Teknik Mesin, 2025)
The development of vocational education demands innovation that can effectively connect theory and practice. This study examines the implementation of the Honda Gamification Program in theoretical and practical learning at a Vocational High School majoring in Motorcycle Engineering. The method used was qualitative, with a literature review of various journals, books, and academic documents related to gamification, learning motivation, and student competency. The results showed that gamification, through the elements of points, levels, challenges, and rewards, increased student motivation, active participation, and skill mastery. The application of gamification also helped create a more challenging and enjoyable learning environment. These findings provide a basis for teachers and schools to integrate gamification into vocational learning strategies that align with industry needs.